STATUS KUALITAS PERAIRAN SUNGAI GAUNG ANAK SERKA KABUPATEN INDRAGIRI HILIR DITINJAU DARI PARAMETER FISIKA, KIMIA PERAIRAN DAN STRUKTUR KOMUNITAS MAKROZOOBENTHOS - Masykur Hz; Syafruddin Nasution; Sofyan Husein Siregar (Jurnal Ilmu Lingkungan, 2009)
Research was conducted in Gaung Anak Serka River Sub-Province Indragiri Hilir in Octobertill januari 2008 as a mean to know status of quality of territorial water of Gaung Anak SerkaRiver evaluated from physics and chemical parameter, and community structure ofmakrozoobenthos. The Method used of survey and intake of sampel taken twice, in each stationof sampel taken at 3 dots at random. Research station consist of; station 1 (GAS river estuary),station 2 (Teluk Pinang), station 3 (Dusun Murni), station 4 (Teluk Pantaian), Station 5 (SungaiIliran), station 6 (Teluk Sungka), station 7 (Tuasan), station 8 (Dusun Pergam), station 9(Sungai Empat) and station 10 (Rambaian). Data has taken of quality of water either throughphysics and chemical parameter and also makrozoobenthos. Data of Exsitu analysed inLaboratory Faculty of Fishery and Marine Science of Riau University. Quality of physics waterparameters (temperature, brightness, deepness, current flow) still normal in a conditionaccording to PP. 82. year 2001, except brightness for station residing in part of downstream(station 1-5) have passed normal sill. Chemical parameters (pH, DO. TSS. COD, BOD, Nitrateand Fospat) also stay in normal gyration. While, organism of Macrozoobenthos found in riverconsist of 6 set of relatives, 5 Class and 6 Ordo. Set of relatives consist of Tucideae,Chironomideae, Baetidae, Ctenodrillidae, Donacidae and Nassariidae. Class coversOligochaeta, Insecta, Polychaeta, Pelecypoda and Gastropoda. Ordo Nematoda, Doptera,Ephemerptera, Ctenodrilida, Veneridea and Neagastropoda. Types of Macrozoobenthos areTubifek sp, Sp Chironomous, Baetis Sp, Ctenodrillus Serratus and Cyclop neritea.